The sensing performance of undoped-AlGaN/GaN/sapphire HEMT hydrogen gas sensor - Mohamad, Mazuina; Fong, Yee Meng; Hashim, Abdul Manaf (2008)
The hydrogen sensing characteristics of undoped-AlGaN/GaN/sapphire circular Schottky diodes are systematically studied and compared over wide hydrogen concentration and temperature ranges. High purity hydrogen gas was exposed to the sample together with the ambient gas of either air or pure nitrogen or without ambient gas (vacuum) at pressure in the range of 50 Torr to 200 Torr was used for both types of ambient gases. The sensing characteristics at different hydrogen concentration are investigated. The sensitivity to hydrogen gas was also investigated in dependence of various catalytic metals thickness and operating temperatures.